LEGAL ISSUES RELATED TO THE SHARIAH ADVISORY COUNCIL IN MALAYSIA - Mohd Yasin, Norhashimah (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2013)
Malaysia has always aspired to be the hub for Islamic banking and finance. Various measures have been, and are being, carried out to promote Malaysia as an international Islamic banking and financial centre. As the backbone for this, the national Shariah Advisory Council (SAC) has been established under the auspices of the Central Bank of Malaysia Act 1958 (CBMA). Under the CBMA, the SAC has been conferred a statutory function as the authority for the ascertainment of Islamic law for the purposes of Islamic banking, as well as business and other types of Islamic financial businesses. In 2009, the CBMA 1958 was replaced and repealed. With the coming into force of the CBMA 2009, the role and functions of the SAC was reinforced and upgraded in terms of appointments of members and, most importantly, that the Shariah rulings pursuant to any reference made to the SAC by the Civil court or arbitrator concerning Shariah matters shall be binding on the Islamic financial institutions as well as on the court and any arbitrator. The issue of whether or not the SAC is the final arbiter on Islamic banking and finance disputes or, in other words, there is no longer a process of judicial review where it involves Shariah matters, will be the highlight of this paper. To what extent does the post CBMA 2009 solve the binding nature of the SAC upon the Civil courts of Malaysia as its rulings and directives are only relevant to âShariahâ issues? What would be the situations if the issues of the Islamic banking and finance cases are deemed not to amount to a âShariahâ issue, but are purely on banking, land matters or contractual interpretations? Has there any actual legal reform been brought about by this amendment or is it merely a cosmetic changes? If the court were to be bound by the SAC rulings, does this not usurp the independence of the judiciary which is the corner stone of the principle of separation of powers between the executive, the legislature and the judiciary? The above legal issues will be critically explored with the help of cases decided by the Malaysian Civil courts, pre and post CBMA 2009.